PENGENDALIAN PERSEDIAAN BAHAN BAKU DENGAN METODE EOQ (ECONOMIC ORDER QUANTITY) DI PT. XYZ PASURUAN - Wahyu, Ika; Wahid, Abdul (Journal Knowledge Industrial Engineering (JKIE), 2018)
Raw materials are the main factor in the company to support the smooth production process, both in large companies and small companies. The problem of determining the amount of demand is an important issue in the company, because inventory has a direct effect on company profits. Mistakes in determining the amount of investment (embedded capital) in inventory will determine the company's profit. The purpose of this study is to find out the number of economical order sizes, reduce storage costs, and know when to make an order. This research is focused on the raw material of button mushrooms produced by PT. XYZ.To predict the number of productions that must be produced in the upcoming period using the moving average and single exponential smoothing method, the data in the previous period. The moving average method uses a moving average of 2,3,4,5 and 6. While a single exponential smoothing Î± = 0.1 - 0.9. The forecasting method used is single exponential smoothing with Î± = 0.8 resulting in a small MAD of 5,381. The result of controlling raw material inventory, the smallest total annual inventory cost is chosen. From here the EOQ model of raw material supply control system is a good raw material inventory control system because it has a total inventory cost of Rp. 8,809,552.29 smaller with a frequency of ordering 9 times when compared to the previous inventory control system of Rp. 12,847,932.69 used by the company. By using the EOQ model, companies can make savings of 31.44%.